Implementasi Nilai-Nilai Islam dalam Pembentukan Karakter Religius Siswa di MTS Al Islam Limpung - Hudiyanti; Aqil Siroj, A. Mustofa; Kurniawan, Rizal; Fuadz, M Nadziful; Noor Syarifah, Nadya Dian; Arum Nita, Tasya (Jurnal Pengabdian Kepada Masyarakat, 2025)
Implementation is the process of carrying out, applying, or realizing a plan, idea, policy, standard, or concept into concrete actions that produce specific impacts or objectives. The implementation of Islamic values in learning at MTs Al Islam. Using a descriptive qualitative approach, data was obtained through observation, interviews with teachers and students, and documentation of learning activities. The results of the study indicate that the implementation of Islamic values is carried out through several strategies. First, instilling faith values through the habituation of worship, such as congregational prayer, Quran recitation, and prayer before and after learning activities. Second, strengthening moral values through teacher role models, fostering politeness, discipline, and respect for parents and teachers. Third, integrating Islamic values into every subject, where teachers link subject matter to Islamic teachings, both in science and social sciences. Fourth, creating a religious environment through the practice of greetings, commemorating Islamic holidays, and Islamic-themed extracurricular activities. The results of this study conclude that MTs Al Islam has successfully implemented Islamic values in a structured and comprehensive manner, thus playing an important role in forming students who are not only academically superior, but also have an Islamic character.